Diversion of methadone and buprenorphine by patients in opioidsubstitution treatment in Sweden : prevalence estimates and risk factors - Johnson, Björn ; 0000-0002-1601-2706; Richert, Torkel (International journal of drug policy, 2015)
Background: Diversion—patients who sell or share their medication—is a hotly debated but rela-tively unresearched phenomenon. We have investigated the prevalence of self-reported diversion ofmethadone and buprenorphine at OST programs in Sweden. We have also examined if demographic,treatment, and social factors can be associated with an increased risk of diversion. Methods: Structured interviews were conducted with 411 patients from eleven OST programs. A standard-ized questionnaire with 106 close- and five open-ended questions were used. 280 interviews were doneon site, by the researchers, while 131 interviews were conducted by specially trained patients throughprivileged access interviewing. The data were analyzed through frequency- and averages-calculations,cross-tabulations, and logistic regression analysis. Results: In total, 24.1% (n = 99) of the patients reported diversion in the past month. 67.6% (n = 277) statedthat they had diverted at some point. The peer interviews showed significantly higher levels of diver-sion (37.4% past month) compared with the researcher interviews (17.2%). Neither demographic factors,dosages, nor collection routines were associated with diversion. The likelihood of diversion was higherfor patients on mono-buprenorphine (OR = 5.64) and buprenorphine–naloxone (OR = 2.10), than amongmethadone patients. Other factors which increased the likelihood of diversion were current illicit druguse (OR = 5.60), having had patients as a primary source of illicit methadone or buprenorphine prior totreatment (OR = 3.39), and mainly socializing with active drug users (OR = 2.12). Conclusion: Self-reported diversion was considerably higher than in previous studies. This is most likelydue to the new methodological strategy we used, but may also partly be explained by low availability ofOST in Sweden, leading to a high demand for the substances by heroin users outside treatment. Effortsto decrease diversion should primarily focus on psychosocial and lifestyle-changing interventions, andexpanded access to treatment, rather than on control measures.
2024-11-19T19:43:38.654+01:00
Keywords: Methadone; Buprenorphine; Diversion; Illicit use; Opioid substitution treatment; Social Work; Socialt arbete